A study on scavenging dpph radical activity of medicinal plants from An Giang - Phan, Thị Anh Đào; Nguyen, Xuân Hải; Nguyen, Trung Nhân; Nguyễn Thị Thanh Mai (Journal of Technical Education Science, 2011)
We carried out a research on the antioxidant activity of 31 extracts prepared from 31 medicinal plants from An Giang province by the DPPH radical scavenging test. 31 extracts displayed activity at 100 µg/ml, 50 µg/ml, 25 µg/ml, and 10 µg/ml. Of the extracts assayed, 21 extracts showed an inhibition rate greater than 50% at 100 µg/ml; 10 extracts had over 50% inhibition at 50 µg/ml; and 5 extracts showed greater than 50% inhibition at 25 µg/ml. Stholobus parviflorus (Roxb.), Excoecaria cochinchinensis Lour showed strong activity tested at smaller concentrations of 1, 2, 5, and 10 µg/ml. IC50 values of these extracts were 5.2 µg/ml and 6.3 µg/ml, respectively. Quercetin was used as a positive control with IC50, 2.2 µg/ml